More shareholders, higher liquidity? Evidence from an emerging stock market - Chia, Yee Ee; Kian-Ping Lim; Kim-Leng Goh (2020)
Using data assembled from all non-financial firms traded on the Malaysian stock exchange, we provide evidence of a nonlinear relationship between the number of shareholders and liquidity. While more shareholders are associated with higher liquidity, the negative effect of wider spreads kicks in when shareholder base exceeds a threshold level due to higher volatility induced by noise trading. However, the threshold level is considerably higher than the number of shareholders of most Malaysian public listed firms, suggesting much room for shareholder expansion in the local market. Our findings call for corporate managers to actively manage and expand their shareholder bases.